Adolescent Curiosity as A Predictor of Sexual Behaviours: Adolescent Curiosity /Sex Behaviour - Attila, Frank Lamadoku; Akpadago , Joseph; Agyei-Sarpong, Kingsley; Eshun, Emmanuel; Inkoom, Daniel; Asamoah-Gyawu, Joseph (International Journal of Rehabilitation and Special Education (IJRSE), 2022)
The study investigated curiosity as a predictor of sexual behaviour among adolescents in fishing communities in the Gomoa West District and Effutu Municipality, Ghana. The study was guided by three research questions. It adopted the quantitative descriptive survey design using two questionnaires; Sexual Curiosity and Sexual Behaviour Scales. Using probability sampling techniques, a sample of 222 senior high school students was selected. The data gathered was analysed descriptively. using frequencies, percentages, and Pearson Product-Moment Correlation. The results showed that there was a significant positive relationship between Curiosity and sexual behaviour among adolescents meaning sexual curiosity, Sexual behaviours among adolescents also increased. With such a revelation, it was assumed that most adolescent students were likely to engage in risky sexual behaviours due to curiosity. The study recommended, among other things, that counsellors and the Ministry of Education plan programmes and activities for adolescents in school to reduce sexual curiosity and as parents also keep their eyes on their children, storing sex-oriented materials away and keeping boys and girls in separate rooms at the domestic level.
Keywords: Adolescent; Curiosity; Sexual behaviours; fishing communities; pre-marital sex; parenting